OVERVIEW OF THE MODULES FOR BUILDING A WIRELESS SENSOR NETWORK: OVERVIEW OF THE MODULES FOR BUILDING A WIRELESS SENSOR NETWORK - Denev , Daniel (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Recent technological advances have enabled the development of low-cost, low-power and multifunctional sensor devices. These nodes are autonomous devices with integrated sensing, processing, and communication capabilities. A sensor is an electronic device that is capable of detecting environmental conditions such as temperature, sound, chemicals, or the presence of certain objects. Sensors are generally equipped with data processing and communication capabilities. The sensing circuitry measures parameters from the environment surrounding the sensor and transforms them into electric signals